Spherical Polyolefin Particles from Olefin Polymerization in the Confined Geometry of Porous Hollow Silica Particles. Issue 20 (24th August 2016) - Freudensprung, Ines; Joe, Daejune; Nietzel, Sven; Vollmer, Doris; Klapper, Markus; Müllen, Klaus
Abstract : Porous hollow silica particles (HSPs) are presented as new templates to control the product morphology in metallocene‐catalyzed olefin polymerization. By selectively immobilizing catalysts inside the micrometer‐sized porous hollow silica particles, the high hydraulic forces resulting from polymer growth within the confined geometries of the HSPs cause its supporting shell to break up from the inside. As the shape of the support is replicated during olefin polymerization, perfectly spherical product particles with very narrow size distribution can be achieved by using HSPs exhibiting a monomodal size distribution. Furthermore, the size of the obtained product particles can be controlled not only by the polymerization time but also by the size of the support material. Abstract : Spherical polyolefin particles with very narrow size distribution are obtained by polymerizing ethylene within the confined geometries of porous hollow silica particles (HSPs) exhibiting a monomodal size distribution. By selectively immobilizing metallocene catalysts inside the micrometer‐sized HSPs, the high hydraulic forces resulting from polymer growth within these "mini‐reactors" cause their supporting shell to break up from the inside.